Gratton effect in the numerical Stroop task is distance dependent. - Shichel, Ido; Goldfarb, Liat (Memory & Cognition, 2026)
In the numerical Stroop task, two digits that vary in both numerical and physical size appear, and participants need to identify which digit has the larger numerical value. Typically, slower responses occur when numerical difference between the digits is small. This finding is known as the distance effect. Slower responses are also noted when numerical and physical sizes are incongruent, known as the size-congruency effect. Additionally, at larger distances, the interfering dimension affects performance less. Furthermore, the size-congruency effect is diminished when the previous trial is incongruent rather than congruent, known as the Gratton effect. The Gratton effect can be explained by several theories, some of which relate to the notion of cognitive control. Based on this idea, the current study investigated whether manipulating task targets through the distance between the numbers influences the appearance of the adaptive control effect, as reflected in the Gratton effect. It examines if the distance in the current trial affects the appearance of the Gratton effect. Both Experiment 1 and Experiment 2 showed that in different settings of the numerical Stroop task, numerical distance influenced the appearance of the Gratton effect, with a more pronounced Gratton effect observed for smaller distances compared with larger ones. This suggests that affecting the task's targets when comparing the two numbers, as indicated by numerical distance, impacted the effect of previous conflicts, with this effect decreasing as comparing the two numbers became easier. These findings are further discussed in the context of cognitive control and numerical processing.